2021
DOI: 10.1186/s12889-021-11544-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personality, alexithymia and work engagement on burnout among village doctors in China: a cross-sectional study

Abstract: Background In China, as the “gatekeepers”of rural residents’ health, the primary-level village doctors, play a very crucial role in ensuring and serving the health level of rural residents. However, the burnout of village doctors is gravely threatening the stability of rural primary medical system step by step. This study systematically evaluated the effects of personality, work engagement and alexithymia on burnout of village doctors, and further measured and assessed the mediating effect of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 49 publications
1
35
0
1
Order By: Relevance
“… 58 , 59 Burnout syndrome affects the health status of health care workers, impacting work commitment and patient safety. 56 , 60 , 61 Consequently, it is imperative that organizations make interventions to prevent the deterioration of the health status of health personnel, which have been magnified by the health emergency. Burnout management should be a means for work engagement, as workers who do not have clear objectives are hesitant to complete tasks and incur less effort and less effective performance from healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“… 58 , 59 Burnout syndrome affects the health status of health care workers, impacting work commitment and patient safety. 56 , 60 , 61 Consequently, it is imperative that organizations make interventions to prevent the deterioration of the health status of health personnel, which have been magnified by the health emergency. Burnout management should be a means for work engagement, as workers who do not have clear objectives are hesitant to complete tasks and incur less effort and less effective performance from healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis indicated that the prevalence of turnover intention of rural primary healthcare workers was about 23.4%−42.1% (28). Other studies had also shown the low job satisfaction of RHWs in China (1,2,31,32). From the existing research, both of them had become an important reason to aggravate the occurrence of turnover behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies directed at RHWs in China also supported that motivation and job satisfaction were inseparable. Under the condition of insufficient objective resources, strong motivation was an important subjective condition to improve job satisfaction and reduce turnover intention (2,14,31,32,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations